Comparison of buccal based triangular flap and lingual based triangular flap on postoperative course after impacted mandibular third molar surgery: a prospective randomized controlled study - Rajendran Balamurugan (EDP Sciences, 2023)
Introduction: The present study is to compare the buccal based triangular flap with lingual based triangular flap on postoperative pain, swelling and trismus after mandibular third molar surgery. Materials and methods: This study comprised of 100 patients, of which, 50 patients underwent buccal based triangular flap technique and 50 patients underwent lingual based triangular flap. The patients in both the groups were evaluated for pain, swelling and trismus on 1st, 3rd and 7th postoperative days. The wound healing was assessed on the 7th postoperative day. The obtained data's were statistically analyzed using SPSS software. Results: Patients in lingual based triangular flap group had less pain on all three postoperative days (P < 0.001). While, the amount of swelling was less on the 3rd postoperative day (P < 0.05) and the degree of trismus was less on 1st and 3rd postoperative days (P < 0.05). The patients in buccal based triangular flap group showed statistical significance for swelling on 1st and 7th postoperative days (P < 0.05) and for trismus on 7th postoperative day (P < 0.05). 2 Patients reported with tissue dehiscence in lingual based triangular flap group. In buccal based triangular flap group, 7 patients presented with wound gaping and 2 patients developed dry socket. Conclusion: Lingual based triangular flap was found to be superior and effective flap design in controlling pain, swelling and trismus with reduced postoperative complications when compared to buccal based triangular flap.